Implikasi Putusan Mahkamah Konstitusi Republik Indonesia Yang Memuat Norma Baru Dalam Sistem Ketatanegaraan Indonesia : Analisis Putusan Mahkamah Konstitusi No. 102/PUU-VII/2009 - Robin Reagan Sihombing; Mirza Nasution; Faisal Akbar; Afnila Afnila (USU LAW JOURNAL, 2019)
Abstract. Based on the provisions of Article 56 and Article 57 of Law Number 8 of 2011 concerning Amendments to Law Number 24 of 2003 concerning the Constitutional Court only limited to the cancellation of the norm (negative legislator). However, from a number of decisions that not only invalidate the prevailing norms, positive legislators are proposed against the limiting bill from the authority of the Constitutional Court. One example of the verdict is the Constitutional Court decision Number 102 / PUU-VII / 2009 which is in the decision of the Constitutional Court (positive legislator), namely by allowing parliamentarians registered in the permanent voters list to be able to choose the identity card and passport. In this case, the authority of the state institution as the legislator of the House of Representatives (DPR) was taken over by the Constitutional Court, therefore the research in this thesis was conducted to explain and analyze the decisions of the Constitutional Court No. 102 / PUU-VII / 2009. The research carried out is normative legal research and the research discussion used is invitational research (statute approach) and renewal (case approach), namely by using legal data sources of secondary data which consists of primary legal materials, secondary legal materials and tertiary legal materials by means of analyzed using qualitative methods to deduce conclusions. Decision of the Constitutional Court No. 102 / PUU-VII / 2009 which influences agreed new norms (positive legislators) is very useful and useful for protecting constitutional rights. real justice. Justice is manifested in a sense of justice that is valued and lives in the midst of society. The implementation of this decision was finally set forth in a law, namely Law No. 7 of 2017 concerning general elections so that the use of identity card or passports in each general election becomes stronger in the implementation of the Court's decision No. 102 / PUU-VII / 2009 can find legal objectives, namely for justice, legal certainty and benefit for the community. Keywords: Mahkamah Konstitusi, constitutional court,  permanent voters list, justice.